Design and validation of the scales of a Spanish-adapted questionnaire to measure pre-service teachers' perceptions about inquiry-based science education - Luque-Jiménez, Jorge; García-Ruiz, Cristina; Lupión-Cobos, Teresa; Blanco-López, Ángel; Blanco-López (Taylor & Francis (International Journal of Science Education), 2024)
This research focused on the pre-service science teachers’ perceptions of Inquiry-Based Science Education (IBSE) in Spanish speaking contexts. Drawing on the PRIMAS questionnaire and extensive adaptations, the PTIP questionnaire, a 25-item instrument was developed to gauge pre-service teachers’ perspectives on IBSE. The questionnaire effectively measures four dimensions through rigorous statistical validation: IBSE teaching practice, IBSE students’ applicability, and internal and external difficulties associated with the inquiry approach. Employing K-means cluster analysis, three distinct profiles emerged, elucidating pre-service teachers’ varying perceptions and readiness to embrace IBSE. Profile A embodies fervent advocates of IBSE, while profile B and C showcases strong support with moderate reservations about its challenges and a more ambivalent stance, respectively. This research contributes a valuable tool for understanding and enhancing pre-service teacher education, fostering the adoption of IBSE
Keywords: Ciencias - Estudio y enseñanza; Profesores - Formación profesional; inquiry-based science education; validity based on internal structure; pre-service teachers